Drug unitarization in a large hospital of Distrito Federal: a pharmacoeconomic analysis - B. Cosma de Souza, Isabela; V. Neves de Oliveira, Ana; Alves Areda, Camila; E. Machado de Oliveira, Rinaldo; L. de Freitas Garcia, Antônio (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: This aimed to do an analysis of the drug unitarization process in a large hospital of Distrito Federal, from a pharmacoeconomical perspective. Methods: This is an observational, retrospective, and descriptive study. It was realized a bibliographic research and a data survey from the local Pharmacotechnical Laboratory, from January 2020 to August 2022. The processes and steps that the medicines went through, from the entry into the hospital up to their distribution, were tracked and registered using a flowchart created with the BizAgi Process Modeler tool. Results: It was verified that the implementation of the unitarization process was simple and low-cost to the hospi tal; There was a significant cost reduction regarding alteplase; as well as a saline and other drugs waste reduction, in addition to a shortage decrease to methylprednisolone. It was found that the records of the unitarization and dispensing processes adopted by the institution aren’t capable yet to secure all the needed traceability to the medicines. Despite that, the unitarization is financially feasible and can reach savings of up to US38,821.92 regarding only one of the drugs, in the appraised period. Conclusions: The pharmacoeconomics impact was positive and the unitarization process led to better results than the drug’s use in its commercial presentations, by reducing possible waste and the possibilities of shortage of the analyzed drugs, improving patient’s safety, and expanding access to the medicines. These results are compatible with other findings available in the literature that attests to the viability of the unitarization process.